ANALISIS REAKSI PASAR MODAL ATAS PERISTIWA KEBIJAKAN AMNESTI PAJAK 2016 (Studi Efisiensi Pasar Modal Indonesia) - Taufika Nur Widyasari; Ifada Faila Suffa; Naili Amalia; Aflit N Praswati (Jurnal Administrasi Bisnis, 2018)
Capital market is a financial instrument that trades securities in the form of bonds and long-term equity issued by the government or private companies that will be bought by investors through the brokers. Capital markets can be affected by changes and developments in economic, political and social variables that will impact on the economic stability of a country. In addition, economic stability in a country can be influenced by government policies, one of which is a tax amnesty program that has been enacted since 2016 by legalizing Law no. 11 Year 2016 on Forgiveness of Taxes. This policy can bring reaction to all companies that listed on Indonesia Stock Exchange (IDX). If an accurate quick reaction occurs to achieve a new equilibrium price that fully reflects the information available, then this market conditions are called efficient markets. This research will discuss about the analysis of capital market’s reaction that happened after the government policy about tax amnesty 2016 in Indonesia Stock Exchange (BEI).